Actividad antimicrobiana in vitro de sustancias producidas por Lactobacillus spp. contra Streptococcus mutans aislado de la cavidad oral de niños sin caries - Pérez-Cubas, Gildert (2025)
Dental caries is a prevalent disease, particularly among the pediatric population, and Streptococcus mutans is a key bacterium involved in its development. This study explores natural alternatives to prevent the colonization of S. mutans in the oral cavity using Lactobacillus spp. strains. The objective was to evaluate the antimicrobial capacity of supernatants obtained from Lactobacillus spp. isolated from vaginal exudate against S. mutans, a bacterium associated with dental caries. Lactobacillus spp. strains were isolated from vaginal exudate, and S. mutans was successfully isolated from three saliva samples collected from children aged 6 to 10 years without dental caries, using Man, Rogosa, and Sharpe (MRS) agar and Mitis Salivarius agar, respectively. Bacterial identification was confirmed by Gram staining and biochemical tests, including catalase, oxidase, and carbohydrate fermentation assays. The antimicrobial activity was evaluated using the disk diffusion method by impregnating sterile disks with Lactobacillus spp. supernatants and placing them on Müller–Hinton agar previously inoculated with S. mutans. Inhibition zones ranging from 10.0 to 13.5 mm were observed in some strains, demonstrating their antimicrobial activity. These results suggest that certain Lactobacillus spp. strains may produce bacteriocins capable of inhibiting S. mutans, highlighting their potential as preventive agents against dental caries and emphasizing the need for further studies to identify strains with the greatest inhibitory capacity.